1990
DOI: 10.1007/bf01437489
|View full text |Cite
|
Sign up to set email alerts
|

Beam-foil lifetime study of Al-like titanium, iron and nickel

Abstract: The lifetimes of the resonance levels in the Al-like ions Ti X, Fe XIV and Ni XVI have been obtained from beam-foil measurements using a variety of analytical techniques. The spectral analysis and identification of cascade transitions necessary for application of the ANDC procedure have been aided by recent observations of laser-produced plasmas. The lifetime values obtained from ANDC analyses for the 3 s 3 p2 doublet levels agree well with predictions based on semi-empirical Hartree-Fock calculations. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…These are compared with the beam-foil measurements of Pinnington et al [16] and the calculations of Aggarwal et al [28], Fawcett [20], and Bhatia and Doschek [13]. The agreement between theory and experiment is within 10% for the lowest 5 levels belonging to the 3s3p 2 configuration.…”
Section: Discussion Of Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…These are compared with the beam-foil measurements of Pinnington et al [16] and the calculations of Aggarwal et al [28], Fawcett [20], and Bhatia and Doschek [13]. The agreement between theory and experiment is within 10% for the lowest 5 levels belonging to the 3s3p 2 configuration.…”
Section: Discussion Of Resultsmentioning
confidence: 88%
“…Träbert et al [7,17] reported lifetimes for high spin 3s3p 2 ( 4 P) and 3s3p3d ( 4 F 0 ) levels in Fe XIV and Ni XVI. Pinnington et al [16] also measured the lifetimes for a few low-lying levels in Ni XVI. Most of the results available in the literature so far are confined to only transitions within the 3s 2 3p, 3s3p 2 , 3s 2 3d, 3p 3 , and 3s3p3d configurations.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There has been extensive laboratory work on Ni XVI and other lines of the Al-like isoelectronic sequence from laser-produced plasma experiments (see, for example, Churilov and Levashov [15], Redfors and Litzén [16]), beam-foil spectroscopy (see, for example, Träbert et al [17], Buchet-Poulizac and Buchet [20], Pinnington et al [21]), spark spectra (Jupén and Curtis [22]), and tokamak spectra (Jupén and Curtis [22], Hinnov et al [19]). Specifically, in Table I the experimental energies were obtained as follows: level 2, from Hinnov et al [19]; levels 7-12, from Shirai et al [14]; levels 4 -6, 13-15, 21-24, and 26 -40, from Churilov and Levashov [15]; level 3, from Redfors and Litzén [16]; levels 16 -18, from Träbert et al [17]; and level 19, from Levashov et al [18].…”
Section: Atomic Datamentioning
confidence: 99%
“…Experiments determining the fine-structure splitting of 3s3p 2 4 P in Al-like ions and for extended analysis of Al-like K VII-Ni XVI spectra up to the 3p 2 3d and 3s3d 2 configurations were performed by Redfors [14] and Churilov [4], respectively. Calculations of transition probabilities for electric dipole transitions between n = 3 doublet levels of Al-like Ti have been tested by lifetime measurements at Bochum [15]. Spectral data and Grotrian diagrams were presented by Kazuo [16] for highly ionized titanium, Ti V-Ti XXII.…”
Section: Introductionmentioning
confidence: 99%